Nigerian national merit awards : award winners' lectures - Nigerian National Merit Award Endowment Fund; Nigerian National Merit Award Endowment Fund. (Ibadan : Spectrum Books Ltd., 1989)
The book contains the lectures delivered by the awardee at the award organised by Nigerian National Merit Lectures in 1989.
usc 03/11/2021
Loans
Keywords: Nigeria